Solving Tracking Problem Of A Nonholonomic Wheel Mobile Robot Using Backstepping Technique - Sulaiman, Noor Asyikin; Md Yusop, Azdiana; Samsudin, Sharatul Izah (Penerbit Universiti, UTeM, 2010)
Nonholonomic system is a mechanical system that is subject to Nonholonomic constraints. They are the contraints on the velocity of the system which cannot be integrated into position constraints that can be used to reduce the number of generalized coordinates. Mobile robots constitute a typical example of non-holonomic systems. This projects attempts to control a nonholonomic mobile robot to track the desired trajectories. In this project, the combination of kinematics and dynamics of the mobile robot are used to control the robot using backstepping technique. Two types of input are presented in this paperwork. From the simulation results, the controller is able to control a non-holonomic mobile robot to track the desired trajectories. All simulations are performed using SIMULINK/MATLAB.